Efecto antibacteriano “in vitro” del extracto hidroalcohólico de Amaranthus hybridus L “Sangorache” sobre la cepa de Lactobacillus acidophilus ATCC 435 - Valverde Haro, Henry Paúl (2016)
The antimicrobial activity of the plants has been evaluated and know since the antiquity, taking as a reference some medicines originated for plans that are used currently inside dentistry, that is why there was the possibility of introducing a study in vitro using a proper Andean plant of our region and continent, through the elaboration of the hidroalcoholic extracts made of leaves and flowers of Amaranthus hybridus L, that were obtained through a maceration process the same ones were tasted qualitative and quantitative, coming across the identification of flavonoids, then the different concentration was done that were 5% 10% 25% 50% and 75%. The extracts of leaves and flowers of sangorache, as well as the alcohol used as negative control and the Clorhexidina to 2% used like positive control, placed in means of cultivation MRS that were containing the vine off lactobacillus acidophilus ATCC 4356 main causative microorganism of injuries of superficial and deep cavities, which as a whole with the streptococcus mutans produce lactic acid from sugar fermentable, therefore they are capable of living in extremely acidic ambiences, by that and antibiogram was realized whit the method (Kirby-Bauer), 24 hours later to the bacterial sowing there was done the measurement of the auras of bacterial inhibition with a rule of antibiogram. The results presentation was done of quantitative form with the analysis of results of a qualitative way using the Duraffourd rules, which indicates a void activity for the extracts hidroalcoholic of Amaranthus hybridus L and negative control for having measurements of the auras of inhibition for below to 8mm, but if sensibility of bacterium exists with Clorhexidina to 2% with auras of bacterial inhibition between 9 and 14 mm.